Simultaneous appraisals of pathway and probable health risk associated with trace metals contamination in groundwater from Barapukuria coal basin, Bangladesh. (March 2020) - Habib, Md Ahosan; Islam, Abu Reza Md Towfiqul; Bodrud-Doza, Md; Mukta, Farhana Afroj; Khan, Rahat; Bakar Siddique, Md Abu; Phoungthong, Khamphe; Techato, Kuaanan
Abstract: In this study, we analyzed 33 groundwater samples from the Barapukuria coal basin (BCB), Bangladesh for 10 trace metals (TMs) using Atomic Absorption Spectroscopy. Pathways and associated probable health risk were appraised by employing multivariate statistical approaches, health risk model and Monte-Carlo simulation. Except for the Cu, Cr and Zn concentrations, the mean concentrations of all TMs in the basin were above the permissible water quality limits set by Bangladesh and international standards. Correlation coefficient and principal component analysis, supported by cluster analysis indicated that anthropogenic inputs were more contributed to the elevated concentrations of TMs compared to geogenic sources as the major reasons of groundwater pollution in the basin. The results of non-carcinogenic risk appraisal depicted that hazard index (HI) values for both adults and children were exceeded the safe limits (>1.0) except for few locations, indicating serious health risks on the human via oral and dermal absorption pathways. However, the carcinogenic risk values of Cd and Cr exceeded the US EPA range of 1 × 10 −6 to 1 × 10 −4, with higher risk for children than adults, with oral intake as the key exposure pathway. A sensitivity study identified the concentration of Cr, exposure frequency and ingestion rate for carcinogenic effect as the most sensitive parameters influencing the probable health risk. Overall, the results suggest that Cr in drinking water could cause detrimental effects to exposed local residents; thus, strict health regulation and groundwater management should concentrate on Cr contamination in groundwater from the coal basin. Graphical abstract: Image 1 Highlights: Groundwater pathways and associated health risks were appraised in the Barapukuria coal basin. Leaching of coal effluences and anthropogenic inputs are the main causes for groundwater pollution. Pb, Cd and Cr are the most hazardous pollutants of the groundwater in the coal basin. Chromium was the predominant contaminant and its carcinogenic risk cannot be ignored. The most sensitive parameter of potential risk was C and EF for adult and IR for children.